Moringa olifera Leaf Meal as an Alternative Protein Feed Ingredient in Broiler Ration - Tesfaye , Etalem; Animut, Getachew; Urge, Mengistu; Dessie, Tadelle (International Journal of Poultry Science, 2013)
A total of 300 Hubbard Classic day-old broiler chicks were randomly distributed into 15 pens equally, representing 5 feeding treatments to evaluate the performance of chicks fed varying dietary levels of Moringa Olifera Leaf Meal (MOLM) replacing soybean meal (SBM) up to the age of 56 days. Treatments were inclusion of MOLM at 0 (T1), 5 (T2), 10 (T3), 15 (T4) and 20% (T5). Four birds 2 from each sex were randomly selected from each replication for carcass evaluation at the end of the study. From the same birds used for carcass evaluation, blood was taken for serum Total Cholesterol (TC) and Total Protein (TP) determination. The crude protein content of MOLM was 28%. Daily Dry Matter (DM) intake during the entire experimental period ranged 54 to 75 g/bird and was greater (P0.05) with T2. Replacement of MOLM for SBM lowered (P